Gambaran Karakteristik Penderita Covid-19 Di Kabupaten Wonosobo - Faizah, Nur; Martini, Martini; Kusariana, Nissa; Muh, Fauzi; Adi, Mateus Sakundarno; Susanto, Henry Setyawan (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
COVID-19 (Coronavirus Disease 2019) is a disease caused by SARS-CoV-2. COVID-19 can be serious and has caused millions of deaths worldwide as well as long-term health problems in some people who have survived. Coronaviruses can be transmitted from person to person. Wonosobo Regency in Indonesia is a regency with local transmission of COVID-19. From 2020 to 2022 confirmed (positive) cases of COVID-19 in Wonosobo Regency was increased. This research conducted by descriptive research using a cross-sectional study design aimed to determine characteristics of COVID-19 recovered patients in Wonosobo Regency. The sample used in this research were 363 respondents selected by probability sampling technic. Characteristics of the respondents were collected by questionnaire, that includes age, gender, type of work, domicile comordities, and symptoms. Characteristics in this study were: age with the largest gap group being early adulthood (26-35 years) of 35,8%: in terms of gender, most of the respondents were male (51%); most of the jobs were self-employed with a percentage of 35,2%; most of the respondents live in Wonosobo District (28,4%); the most common accompanying conditions was in patients with hypertension (3,3%), the most common symptom condition was fever (68,3%).The government can make policies that are more targeted in the prevention and control of COVID-19.